PENGARUH LEVERAGE, LIKUIDITAS, UKURAN PERUSAHAAN, DAN KUALITAS AUDIT TERHADAP KUALITAS INFORMASI LAPORAN KEUANGAN - Susanti Susanti (Universitas Sarjanawiyata Tamansiswa, 2017)
The purpose of this study was to examine issues relating to the measurement of the quality of empirical studies of financial statement information on the company property and real estate the period 2008-2011 . This study use the four independent variables , namely , leverage , liquidity , firm size , and audit quality and the use of the dependent variable as a proxy for the quality of the timeliness of financial information.This study uses targeted Sampling (purposive sampling) . Population in this research is that companies engaged in property and real estate are listed in the Indonesia Stock Exchange during the study period between 2008 to 2011 . Sample totaled 128 with 32 companies that have been based on the criteria specified . Analysis of research data using multiple linear regression with SPSS Version 16.0 .Based on the analysis performed in this study shows that of the four proposed variables (leverage , liquidity , firm size , and quality audit) only liquidity that have a significant positive impact on the quality of financial reporting information , while leverage , firm size , and quality audit is not affect the quality of financial reporting information.Keyword:Â leverage, liquidity, firm size, audit quality, timeliness.